2020
DOI: 10.1155/2020/5437376
|View full text |Cite
|
Sign up to set email alerts
|

Development of Swallowing Function in Infants with Oral Feeding Difficulties

Abstract: Background. Discharge of preterm infants is often delayed because of their oral feeding difficulties. Independent oral feeding is the last obstacle to pass after managing acute and chronic morbidities. We conducted this study to determine the prevalence, characteristics, and risk factors of swallowing dysfunction and suggest proper interventions to reduce aspiration and chronic lung injury. Methods. Infants admitted to the neonatal intensive care unit (January 2016 to December 2018) who were performed modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Independent oral feeding requires sophisticated control of numerous phases, including sucking, swallowing, breathing, maturation of respiratory function to endure short pauses of ventilation during swallowing, and coordination of the suck-swallow-breathe cycle [ 9 , 10 , 22 , 23 ]. Studies have shown that 50%–60% of preterm infants with feeding desaturation exhibit swallowing dysfunction in video-fluoroscopic swallowing tests at term-equivalent age [ 11 , 24 ]. Further, thickened liquids were slower to reach the hypopharynx and remained there for a shorter period of time, improving swallowing function and safety in neurologically impaired patients such as those with cerebral palsy, brain damage, and neurodegenerative diseases [ 25 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Independent oral feeding requires sophisticated control of numerous phases, including sucking, swallowing, breathing, maturation of respiratory function to endure short pauses of ventilation during swallowing, and coordination of the suck-swallow-breathe cycle [ 9 , 10 , 22 , 23 ]. Studies have shown that 50%–60% of preterm infants with feeding desaturation exhibit swallowing dysfunction in video-fluoroscopic swallowing tests at term-equivalent age [ 11 , 24 ]. Further, thickened liquids were slower to reach the hypopharynx and remained there for a shorter period of time, improving swallowing function and safety in neurologically impaired patients such as those with cerebral palsy, brain damage, and neurodegenerative diseases [ 25 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10,22,23) Studies have shown that 50-60% of preterm infants with feeding desaturation exhibit swallowing dysfunction in video-fluoroscopic swallowing tests at term-equivalent age. 11,24) Further, thickened liquids were slower to reach the hypopharynx and remained there for a shorter period of time, improving swallowing function and safety in neurologically impaired patients such as those with cerebral palsy, brain damage, and neurodegenerative diseases. [25][26][27] In addition, adapting the flow rate has been shown to have positive effects on sucking patterns and suck-swallowbreathe coordination.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 3 more Smart Citations